A method to evaluate the Fusarium moniliforme var. subglutinans dissemination in pineapple - Mattos, Aristóteles Pires de; Aguilar, Juan Angel Espinal; Neiva, Luiz Paulo Almeida (Pesquisa Agropecuaria Brasileira, 2014)
A trial was carried out to determine a method to detect the aerial dispersal of Fusarium moniliforme var. subglutinans spores. Petri dishes, containing a Fusarium spp. selective medium developed by Nash & Snyder, were randomly placed in different positions, directions and periods of sun exposure. This method showed to be efficient, but there was no significant difference between the number of propagula colonies captured and the various positions and directions of the dishes. As to the period of sun exposure, no spores were captured after the eight hour period. It was observed, through the pathogenicity test, that the colonies identified as F. monoliforme var. subglutinans were 100% pathogenic to the pineapple plants.